Subsídios para o diagnóstico das pontes do sistema viário do município de Pato Branco - Paraná - Milani, Cleovir José (2010)
Infrastructure is an indispensable and decisive requirement for the economic development of a country; it is directly linked to the set of structural economic activities and serves as the foundation for the development of other activities. Among the many works of infrastructure, the bridges have fundamental importance to the development of the cities, economically and socially speaking, because the roads are to ensure the entry of inputs on farms, as well as the disposal of products and free movement of populations. The aim of this study is to present a survey of the existing bridges in Pato Branco, Paraná State, identifying the most recurrent damages, in order to provide grants to administrators, seeking to ensure the correct functioning of the transport infrastructure and in the preservation of public property and security for the users. For this purpose, the method used for inspections and surveys of the bridges was guided by the Technical Standards 010/2004 - PRO DNIT and NBR 9452 (1986) ABNT. Data collection was conducted through visits, using the method of visual and photographic records. After the survey was done, we identified several pathological manifestations, both in concrete and wood bridges, such as moisture stains, cracks, corrosion, erosion, clogging of drains; wood decay, lack of verticality of the pillars and foundation repression, among others. Moreover, there was little or no maintenance on the existing bridges. Finally, we can say that the methodology used was appropriate since it provided a coherent survey of the situation concerning the bridges of the city